SISTEM PENGAJARAN PERSPEKTIF ABDUL MUTHALIB MUHYIDDIN DALAM KITAB SENDI IMAN - Al-Mukhdi, M. Nafis (Taklim : Jurnal Pendidikan Agama Islam, 2024)
AbstractThis research is grounded in the premise that education's primary objective is to uphold the oneness of God, which requires educators to be skilled in implementing teaching systems. Abdul Muthalib Muhyiddin, in his book Sendi Iman, first published in 1971, also presented a teaching theory, the relevance of which needs to be explored. The aim of this study is to examine Abdul Muthalib Muhyiddin's perspective on teaching systems in Sendi Iman and its relevance to contemporary teaching theories. The study employs a literature review method, encompassing both analysis and synthesis stages. The findings indicate that, according to Abdul Muthalib Muhyiddin, there are five stages of teaching: introduction, statement (explanation), comparison, opinion (conclusion), and application (tathbiq). The planning process involves determining the subject matter, teaching methods, target class, designated time for teaching, objectives of the lesson, and teaching aids. The goal of teaching is for students to independently acquire knowledge and benefit from it as easily as possible. For teaching materials, Abdul Muthalib used Sendi Iman. The teaching methods include lectures, question-and-answer sessions, assignments, recitation, examples, and step-by-step progression. Assessment, as practiced by Abdul Muthalib, is limited to reviewing the day’s lesson. Teaching skills identified include starting and concluding lessons, explaining material, questioning, providing reinforcement, using instructional media, and classroom management.Keywords: Teaching Stages,  Learning Methods, Islamic Education, Abdul Muttalib Muhyiddin, Book of Sendi ImanAbstrakPenelitian ini bertolak dari latar belakang bahwa pendidikan memiliki tujuan utama untuk menjunjung tinggi keesaan Tuhan dan dalam mewujudkannya diperlukan pendidik yang memiliki kepiawaian dalam menerapkan sistem pengajaran. Abdul Muthalib Muhyiddin dalam Kitab Sendi Iman yang pertama kali dicetak pada tahun 1971 turut menyampaikan teori pengajaran sehingga perlu diketahui relevansinya. Penelitian ini bertujuan untuk mengetahui bagaimana sistem pengajaran perspektif Abdul Muthalib Muhyiddin dalam kitab Sendi Iman dan relevansinya dengan teori pengajaran. Penelitian ini menggunakan metode kepustakaan yang melalui tahapan analisis dan sintesis. Hasil penelitian menyatakan bahwa dalam perspektif Abdul Muthalib Muhyiddin, ada lima tahapan pengajaran yakni pendahuluan, menyatakan (menerangkan), perbandingan, pendapat (kesimpulan), dan persesuaian (tathbiq). Perencanaan terdiri dari mata pelajaran, methodie (cara) mengajar, kelas berapa akan mengajar, waktu yang ditentukan untuk lamanya mengajar, maksud pelajaran itu, dan alat-alat untuk menerangkan pelajaran. Tujuan pengajaran adalah murid dapat berfikir sendiri mencapai pengetahuan dan mengambil faedahnya dengan semudah-mudahnya. Untuk bahan ajar, Abdul Muthalib menggunakan Kitab Sendi Iman. Metode mengajar terdiri dari ceramah, tanya jawab, pemberian tugas dan resitasi, perumpamaan, dan pentahapan. Penilaian yang dilakukan Abdul Muthalib sebatas menanyakan ulang pelajaran pada hari itu. Keterampilan mengajar yang dinyatakan yakni membuka dan menutup pelajaran, menjelaskan materi, bertanya, memberi penguatan, menggunakan media pengajaran, serta mengelola kelas. Kata kunci : Tahapan Pengajaran, Metode Pembelajaran, Pendidikan Islam, Abdul Muttalib Muhyiddin, Kitab Sendi Iman